Caulobacter crescentus: caracterização, expressão heteróloga e aplicações biotecnológicas do gene celA - Bussler , Larissa (2019)
In recent years, studies have advanced to improve in biotechnological interest the enzymes expression in bacteria. Numerous enzymes involved in the metabolism of lignocellulosic materials are produced by Caulobacter crescentus, a Gram-negative aquatic bacterium that survives in oligotrophic environments and has a single gene called celA encoding cellulase (E.C. 3.4.2.1). Thus, the celA gene (CCNA: 02310) from C. crescentus was cloned and overexpressed in Escherichia coli, the recombinant protein produced, was purified by affinity chromatography using nickel-Sepharose resin. The protein was then subjected to biochemical characterization and industrial applications in the hydrolysis of agricultural residues and in the Denim fabric biopolymerization. In order to induce cellulase parental strain C. crescentus (NA1000), the bacteria were cultivated in minimal medium (M2) supplemented with 1% (w/v) corn stover (CS) or corn cob (CC). The highest cellulase activity of 6.44 U.mL-1 was verified in the presence of CS after 18 h of assay and 1.81 U.mL-1 in CC. In CS, the cellulase activity remained higher to 48 h with 3.84 U.mL-1, about 12 times higher than observed with the addition of CC, in which the activity was considered null after 24 h of assay. Sequencing of cloned celA gene confirmed 99% homology to cellulase of C. crescentus, belonging to glycohydrolases (GH) family 9, according to CAZy. The predicted protein encodes 625 amino acids and has a weight mass of 73 KDa. Overexpression was analyzed by the SDS-PAGE gel, which protein purification showed a single band at the expected height, confirmed by viewing a halo of activity on the PAGE-activity gel. Biochemical characterization of the purified protein showed optimum pH and stability pH 5.5 and 6.0, respectively, with a pI of 6.0. The optimum temperature was obtained at 40 °C, and thermostability of CelA showed a half-life time of 1 hour at optimum temperature. At 35 °C, the enzyme lost about 20% of its activity within 240 minutes of assay. Substrate specificity confirmed that the enzyme is an CMCase, having affinity to carboxymethylcellulose (CMC), represented by amorphous cellulose. The addition of MnCl2 (2 mM) led to an increased cellulase activity by 70%. In contrast, contact HgCl2 and AgCl2 (2 mM) the enzyme retained only 50 and 40% activity respectively. The kinetics of CelA for CMC presented a KM of 0.66 mg.mL-1 and VMax of 2.41 U.mg.mL-1, and Kcat 2.94 s -1. For the kinetics in the presence of the MnCl2 ion, at the 5 mM concentration, the KM was 1.20 mg.mL-1 and VMax of 3.11 U.mg.mL-1, and Kcat 3.78 s -1. The enzyme purified under optimized conditions, presented a higher rate of hydrolysis of CS, producing 2,62 μmol.mL-1 , around 2,5 times greater in contact with CC produced 1.02 μmol.mL-1 of reducing sugars in 24 hours assay. The application of CelA to Denim fabric bio-polishing showed interest results for the removal of fibrils, fuzz and cellulose pills from the Denim fabric at 40 °C at pH 5.5 for 12 hours. The action of the enzyme generated a minimal weight loss (> 3%) of 2.43% and 2.17 μmol.mL-1 reducing sugar in the process. The morphological changes of Denim were observed by SEM images (increase in 5x), which confirmed the cellulase action in the treated fabric. The enzyme was successfully characterized, making this the first report in literature about cellulase C. crescentus. The enzyme cellulase application in agricultural waste confirmed that PM is an interesting carbon source for production of fermentable sugars, contributing to the bioethanol chain. The enzyme’s action in the Denim fabric confirms the potential for bio-treatment of cotton-based fabric, being an interesting substitute for chemical washes, improving the finishing and quality of fabric in an economical and environmentally friendly manner.